Social Media and its Effects on Mental Health - Sonu Vatsa; Mrigakshika Sharma; Lali Koptonashvili (European Scientific Journal, ESJ, 2020)
There is no doubt that varioussocial media platforms have transformed the new generation. The social media has resulted in the transformation of not only how this generation communicates, but has also transformed business, education and above all, the entertainment. Not only that the social media has made a lot of positive impacts on the human life, it has a lot of negative impacts on all age group as well, especially the youth. Addiction of social media is in trend and is a major contributing factor to rapid increase in several mental health issues. Some of the examples of the issues arising from the excessive use of social media that are on rise include: disturbed circadian rhythm, sleep disorders, reproductive health, phantom vibration, and ringing syndrome. Therefore, thisstudy surveyed the extent to which the mental health is being hampered by excessive use ofsocial media. This study was conducted in two stages surveying 263 participants from India, Russia, Nepal, Ukraine, Kazakhstan, and Georgia. A questionnaire was used as a research instrument, which was sent to the random respondents to study their indulgence in social media. Findings from these responses showed that the mental health issues are associated to the social media usage. Therefore, stakeholders must take remedial action to prevent rampancy of social media usage. From the study conducted, the effects of the social media are not only taking toll on the social life, life style, and physical heath of the users but, also over their mental health. There are urgent needs to take immediate remedial measures to counter this growing menace in the society.